2008
DOI: 10.1063/1.2918842
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-mediated dopant diffusion activation enthalpies for germanium

Abstract: Electronic structure calculations are used to predict the activation enthalpies of diffusion for a range of impurity atoms ͑aluminium, gallium, indium, silicon, tin, phosphorus, arsenic, and antimony͒ in germanium. Consistent with experimental studies, all the impurity atoms considered diffuse via their interaction with vacancies. Overall, the calculated diffusion activation enthalpies are in good agreement with the experimental results, with the exception of indium, where the most recent experimental study su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
116
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 41 publications
11
116
2
Order By: Relevance
“…5 The diffusion experiments reported by Dorner et al, 17,20 Södervall et al, 18 and Riihimäki et al 19 yield diffusion activation enthalpies for Al, Ga, and In that clearly exceed the activation enthalpy of self-diffusion. 21,22 Considering the DFT calculations of Chroneos et al, 23,24 these results seem to be in conflict with the picture on a vacancy-mediated acceptor diffusion that predict diffusion activation enthalpies below 3 eV for Al, Ga, and In. In order to verify the diffusion activation enthalpy, we report in this paper experiments on the intrinsic and extrinsic diffusion of In in Ge.…”
Section: Introductioncontrasting
confidence: 52%
See 1 more Smart Citation
“…5 The diffusion experiments reported by Dorner et al, 17,20 Södervall et al, 18 and Riihimäki et al 19 yield diffusion activation enthalpies for Al, Ga, and In that clearly exceed the activation enthalpy of self-diffusion. 21,22 Considering the DFT calculations of Chroneos et al, 23,24 these results seem to be in conflict with the picture on a vacancy-mediated acceptor diffusion that predict diffusion activation enthalpies below 3 eV for Al, Ga, and In. In order to verify the diffusion activation enthalpy, we report in this paper experiments on the intrinsic and extrinsic diffusion of In in Ge.…”
Section: Introductioncontrasting
confidence: 52%
“…This has been concluded from self-and foreign-atom diffusion studies 7,21,22,[27][28][29][30] and confirmed by atomistic calculations. 15,23,[30][31][32][33] In particular, the simultaneous diffusion of self-and dopant atoms in isotopically controlled Ge heterostructures have revealed that vacancies in Ge are mainly doubly negatively charged under intrinsic and n-type doping conditions. 7,34 However, the preferred charge state of V under p-type doping is not known.…”
Section: B Motivation Of Diffusion Model and Numerical Simulationsmentioning
confidence: 99%
“…[1][2][3][4][5] An enabling factor is the advent of high dielectric constant (high-k) dielectrics that allow the departure from the prerequisite to use native oxides such as SiO 2 in Si-based devices. [6][7][8] Si 1-x Ge x is a random alloy with the diamond structure that has one lattice site that can be occupied by either Si or Ge.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent theoretical calculations of the activation enthalpy of P, As, and Sb diffusion in Ge not only reproduce the decreasing diffusion activation enthalpy with increasing size of the dopants but also agree quantitatively with the experimental results. 10 Uberuaga et al 11 predicted an activation enthalpy of 3.1 eV for Ge self-diffusion that is in excellent agreement with the experimental result of 3.09 eV reported by Werner et al 8 This agreement between experimental and theoretical results on the activation enthalpies of self-and dopant diffusion holds true for Ge and also for Si ͑see below͒ in the case an alternative functional, such as the B3YLP, is used in density functional theory ͑DFT͒ calculations, as discussed by Uberuaga et al 11 Previous DFT calculations 3-5 are known to underestimate the formation energies of defects in Si and Ge due to the lack of exact exchange in these functionals. [12][13][14][15] Although these are well converged studies employing supercells of up to 512 atoms and Brillouin-zone sampling with 2 3 k-points, the 3.17-3.29 eV values predicted for the V-formation enthalpy in Si 3,5 are a severe underestimation and are therefore not appropriate to facilitate comparison with the experimental studies that support 3.6 eV for selfdiffusion via V in Si.…”
mentioning
confidence: 99%